Photovoltaic Performance Enhancement of Silicon Solar Cells Based on Combined Ratios of Three Species of Europium-Doped Phosphors - Wen-Jeng Ho (Materials, 2018)
This paper presents a scheme for the enhancement of silicon solar cells in terms of luminescent emission band and photovoltaic performance. The proposed devices are coated with an luminescent down-shifting (LDS) layer comprising three species of europium (Eu)-doped phosphors mixed within a silicate film (SiO2) using a spin-on film deposition. The three species of phosphor were mixed at ratios of 0.5:1:1.5, 1:1:1, or 1.5:1:0.5 in weight percentage (wt %). The total quantity of Eu-doped phosphors in the silicate solution was fixed at 3 wt %. The emission wavelengths of the Eu-doped phosphors were as follows: 518 nm (specie-A), 551 nm (specie-B), and 609 nm (specie-C). We examined the extended luminescent emission bands via photoluminescence measurements at room temperature. Closely matching the luminescent emission band to the high responsivity band of the silicon semiconductor resulted in good photovoltaic performance. Impressive improvements in efficiency were observed in all three samples: 0.5:1:1.5 (20.43%), 1:1:1 (19.67%), 1.5:1:0.5 (16.81%), compared to the control with a layer of pure SiO2 (13.80%).